2004
DOI: 10.4049/jimmunol.172.8.5006
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Serum Amyloid A-Activating Factor 1 Inhibits Cell Proliferation by the Induction of Cyclin-Dependent Protein Kinase Inhibitor p21WAF-1/Cip-1/Sdi-1 Expression

Abstract: Inflammation-responsive transcription factor, serum amyloid A-activating factor 1 (SAF-1), has been shown to regulate several genes, including serum amyloid A, γ-fibrinogen, and matrix metalloproteinase 1, whose abnormal expression is associated with the pathogenesis of arthritis, atherosclerosis, and amyloidosis. Prolonged high level expression of SAF-1 in cultured cells failed to produce any stable cell line that overexpresses SAF-1. To test the fate of SAF-1-overexpressing cells, the cells were monitored fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Unlike GFP-expressing cells, we observed that the percentage of cells with high-level of p53R2-GFP expression progressively decreased among G418-resistant cells during the process of selection and following culture with G418. The phenotype of p53R2-GFP expressing cells during G418-selection was very similar to cells overexpressing cell cycle inhibitor as reported previously by others (21, 24). Overexpression of GFP may be cytotoxic to cells; however, the phenomena may not be caused by GFP, since the intensity and viability of GFP-expressing cells were stable during G418-selection and culture.…”
Section: Discussionsupporting
confidence: 86%
“…Unlike GFP-expressing cells, we observed that the percentage of cells with high-level of p53R2-GFP expression progressively decreased among G418-resistant cells during the process of selection and following culture with G418. The phenotype of p53R2-GFP expressing cells during G418-selection was very similar to cells overexpressing cell cycle inhibitor as reported previously by others (21, 24). Overexpression of GFP may be cytotoxic to cells; however, the phenomena may not be caused by GFP, since the intensity and viability of GFP-expressing cells were stable during G418-selection and culture.…”
Section: Discussionsupporting
confidence: 86%
“…Next, we searched the IPA PPI database for interactions linking the pathways, and we identified the MAZ transcription factor, which, incidentally, was also one of the most enriched transcription factors in the promoter enrichment analysis. Specifically, MAZ activates expression of CDKN1A (a component of the CHK pathway and a ‘Cell Cycle’ subnetwork hub), thereby controlling cell cycle progression through the G1 checkpoint [38] (see also Figure 5). MAZ is also activated by both IL1 and IL6 through MAP kinase-dependent phosphorylation in human cells [39] and is a member of the MYC complex.…”
Section: Resultsmentioning
confidence: 99%
“…MAZ increases cyclin-dependent kinase inhibitor 1A (CDKN1A) expression [38] and is known to regulate MYC transcription [45] – two molecules with seemingly opposed effects on cell cycle. Increased CDKN1A transcription leads to cell cycle arrest and the production of serum amyloid A (SAA), which in turn leads to increased recruitment of immune cells to inflammatory sites [38,39,46]. Increased MYC transcription is most often associated with increased proliferation but it has also been linked to increased cell cycle arrest in fibroblasts [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, whenever possible, viral side effects should be excluded by using the appropriate controls such as mock transduction or using a control marker without any deleterious function on the target cell. Non-viral strategies such as the calcium phosphate method [23] or lipofection [12,46] are also very useful, but some cells can not or only to a lower extent be transduced by this methods. These experimental achievements may also be the basis for future gene therapy for human arthritides [47,48].…”
Section: Transductionmentioning
confidence: 99%
“…At present, cDNA arrays are commercially available from several companies [16,17,[20][21][22][23] or they can be custom-made including the specific genes of interest [13]. As alternative to the nylon arrays, glass or plastic arrays can be used.…”
Section: Microarraysmentioning
confidence: 99%